The Influence of Corporate Social Responsibility Disclosure, Accounting Conservatism, Earnings Persistence, and Systematic Risk on Earnings Response Coefficient (ERC) - Yuliandhari, Willy Sri; Fadila, Egita Nur (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Earnings response coefficient is a valuation model used to show the probability of fluctuations in share value as a result of market reactions to earnings information presented by companies issuing shares. The phenomenon that occurred in this research was found in several companies where stock price movements and profits were not in line. This research aims to determine the effect of disclosure of corporate social responsibility, conservatism, earnings persistence and systematic risk on mining companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2023 period simultaneously and partially. This research uses quantitative methods and purposive sampling. The analysis model used is a panel data regression analysis model with Eviews 12 analysis software. The research results state that corporate social responsibility (CSR) disclosure, conservatism, earnings persistence and systematic risk have a negative and significant effect on the earnings response coefficient.